Chemical composition and antioxidants potential of extracts of yellow melon seeds in Soybean oil - Roberta Malacrida, Cassia [UNESP]; Milene Angelo, Priscila [UNESP]; Andreo, Denise [UNESP]; Jorg, Neuza [UNESP] (Univ Federal Ceara, 2007)
The aim of this work was to characterize the yellow melon seeds, hybrid variety, as for their proximate composition, and to evaluate the antioxidant potential of extracts of seed in soybean oil. The extract of melon seeds (EM), obtained by extraction using ethanol: water (95:5), was applied in soybean oil at three different concentrations (500; 750 and 1000 mg kg(-1)) and submitted to Shaal oven method at 60 degrees C for 20 days. Oil samples were evaluated for peroxic a value in periods of five days. The antioxidant activity of the extract was compared to the BHT (butyl-hydroxytoluene) activity. The melon seeds showed a high nutrition value, containing high percentages of lipids (25.2%), proteins (20.1%) and fiber (30.0%). All these treatments retarded lipid oxidation in soybean oil; however the natural extracts were less effective than BHT after 10 days in the oven. The antioxidant activities of different treatments tested in this study followed the order: BHT > EM 1000 mg kg(-1) = EM 750 mg kg(-1) > EM 500 mg kg(-1)> control.
Keywords: Cucumis melo; vegetable oil; peroxide value